Artificial Intelligence and the Emergence of Co-Creativism in Contemporary Art - Tace McNamara (INSAM)
This paper argues for the emergence of a new art movement termed Co-Creativism, emblematic of the profound synergy between humans and artificial intelligence (AI) in shaping artistic narratives. Emerging as a successor to post-postmodernism and metamodernism, I propose Co-Creativism began its ascent around 2018 and has since solidified its prominence by 2023, notably influenced by the post-COVID landscape. The era transcends viewing AI as a mere instrumental entity, instead recognising it as an integral co-contributor in the creative realm. Through a methodical approach encompassing case studies and content analysis of artist statements, this paper aims to define the key characteristics and underlying themes of Co-Creativism. By examining the interplay between the global context, the art world, the notion of the artist, art-making practice, the audience, and co-creativist art, the goal is to provide a comprehensive understanding of Co-Creativism.